Optimization of the national economy structure as a fulfilment of objectives of the strategic course of Russia - E. A. Stepin (Путеводитель предпринимателя)
The author considers the prospects for socio-economic development of Russia and raises the question about the necessity of the optimization of the national economy structure in terms of the sanctions policy realized by the Western countries.